Conformal Metamaterials with Active Tunability and Self-Adaptivity for Magnetic Resonance Imaging - Ke Wu; Xia Zhu; Xiaoguang Zhao; Stephan W. Anderson; Xin Zhang (Research)
Metamaterials hold great potential to enhance the imaging performance of magnetic resonance imaging (MRI) as auxiliary devices, due to their unique ability to confine and enhance electromagnetic fields. Despite their promise, the current implementation of metamaterials faces obstacles for practical clinical adoption due to several notable limitations, including their bulky and rigid structures, deviations from optimal resonance frequency, and inevitable interference with the radiofrequency (RF) transmission field in MRI. Herein, we address these restrictions by introducing a flexible and smart metamaterial that enhances sensitivity by conforming to patient anatomies while ensuring comfort during MRI procedures. The proposed metamaterial selectively amplifies the magnetic field during the RF reception phase by passively sensing the excitation signal strength, remaining “off” during the RF transmission phase. Additionally, the metamaterial can be readily tuned to achieve a precise frequency match with the MRI system through a controlling circuit. The metamaterial presented here paves the way for the widespread utilization of metamaterials in clinical MRI, thereby translating this promising technology to the MRI bedside.